2013
DOI: 10.3899/jrheum.130170
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Zoster Vaccination in SLE: A Pilot Study of Immunogenicity

Abstract: Background Patients with systemic lupus erythematosus (SLE) are at increased risk of herpes zoster (HZ). Although a vaccine for HZ has been FDA approved, its use in immunocompromised individuals remains controversial because it is a live-attenuated virus vaccine. We performed a pilot study of the immunogenicity of Zostavax® in SLE patients. Methods Ten SLE patients and 10 controls ≥50 years old participated in this open label vaccination study. All were seropositive for varicella zoster virus (VZV). SLE pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 17 publications
2
36
0
8
Order By: Relevance
“…A large study that used the Medicare database for patients with inflammatory arthritis confirmed that the herpes zoster vaccine reduced the risk of herpes zoster by 40% in 2 years, and no such cases had occurred in patients exposed to bDMARDs at the time of vaccination or within the subsequent 42 days [122]. In a small open study of herpes zoster vaccination, 10 patients with SLE had low disease activity and received low-dose corticosteroids, hydroxychloroquine, or MTX, and none developed herpes zoster within 12 weeks post vaccination [172].…”
Section: Vaccination In Patients With Ards and Possible Induction Of mentioning
confidence: 87%
“…A large study that used the Medicare database for patients with inflammatory arthritis confirmed that the herpes zoster vaccine reduced the risk of herpes zoster by 40% in 2 years, and no such cases had occurred in patients exposed to bDMARDs at the time of vaccination or within the subsequent 42 days [122]. In a small open study of herpes zoster vaccination, 10 patients with SLE had low disease activity and received low-dose corticosteroids, hydroxychloroquine, or MTX, and none developed herpes zoster within 12 weeks post vaccination [172].…”
Section: Vaccination In Patients With Ards and Possible Induction Of mentioning
confidence: 87%
“…Biological agents in particular have been associated with the reactivation of latent infectious processes, which may be viral or bacterial; tuberculosis reactivation remains a significant problem in immunomodulatory therapy 3. Although VZV vaccines exist, their routine use in immunosuppressed patients remains controversial—largely because they are high-potency live vaccines 4. There is currently no unified guidance regarding vaccination in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these very young patients with LN are at high risk of herpes zoster, with risk relatively higher than patients with noninflammatory musculoskeletal conditions 99 . Herpes zoster is a potentially preventable disease by the use of a vaccine, and patients with SLE mount a good immune response to this vaccine 100 . Given the availability of a vaccine to prevent herpes zoster, we believe that zoster vaccination should be administered prior to immunosuppressive initiation.…”
Section: Discussionmentioning
confidence: 99%